Indicators of Safety Compromise in Gastrointestinal Endoscopy. (2012) - Borgaonkar, Mark R; Hookey, Lawrence; Hollingworth, Roger; Kuipers, Ernst J; Forster, Alan; Armstrong, David; Barkun, Alan; Bridges, Ronald; Carter, Rose; de Gara, Chris; Dube, Catherine; Enns, Robert; et al.
Abstract : The growth in the use of endoscopy to diagnose and treat many gastointestinal disorders, and its central role in cancer screening programs, has led to a significant increase in the number of procedures performed. This growth, however, has also led to many variations in, among others, the provision of services, the choice of sedative medications and the training of providers. The recognition of the significance of quality in endoscopy has prompted several countries, including Canada, to initiate efforts to adopt nationwide quality improvement programs. The Canadian Association of Gastroenterology formed a committee to review endoscopy and quality with the aim of stimulating improvement. This article focuses specifically on patient safety indicators that were developed at a consensus conference aimed at generating a broad range of recommendations for selected endoscopic procedures, which if adopted, could lead to significant changes in how endoscopy services are provided. Abstract : INTRODUCTION: The importance of quality indicators has become increasingly recognized in gastrointestinal endoscopy. Patient safety requires the identification and monitoring of occurrences associated with harm or the potential for harm. The identification of relevant indicators of safety compromise is, therefore, a critical element that is key to the effective implementation of endoscopy quality improvement programs. OBJECTIVE: To identify key indicators of safety compromise in gastrointestinal endoscopy. METHODS: The Canadian Association of Gastroenterology Safety and Quality Indicators in Endoscopy Consensus Group was formed to address issues of quality in endoscopy. A subcommittee was formed to identify key safety indicators. A systematic literature review was undertaken, and articles pertinent to safety in endoscopy were identified and reviewed. All complications and measures used to document safety were recorded. From this, a preliminary list of 16 indicators was compiled and presented to the 35-person consensus group during a three-day meeting. A revised list of 20 items was subsequently put to the consensus group for vote for inclusion on the final list of safety indicators. Items were retained only if the consensus group highly agreed on their importance. RESULTS: A total of 19 indicators of safety compromise were retained and grouped into the three following categories: medication-related – the need for CPR, use of reversal agents, hypoxia, hypotension, hypertension, sedation doses in patients older than 70 years of age, allergic reactions and laryngospasm/bronchospasm; procedure-related early – perforation, immediate postpolypectomy bleeding, need for hospital admission or transfer to emergency department from the gastroenterology unit, instrument impaction, severe persistent abdominal pain requiring evaluation proven to not be perforation; and procedure-related delayed – death within 30 days of procedure, 14-day unplanned hospitalization, 14-day unplanned contact with a health provider, gastrointestinal bleeding within 14 days of procedure, infection or symptomatic metabolic complications. CONCLUSIONS: The 19 indicators of safety compromise in endoscopy, identified by a rigorous, evidence-based consensus process, provide clear outcomes to be recorded by all facilities as part of their continuing quality improvement programs.